Computerized assignment / project submission system for F.S.K.T.M. - Phillomeana, Anak Limbang (Universiti Malaysia Sarawak, UNIMAS, 2006)
A good system is needed to manage the submission of student assignment/project at the university. The manual system needs to be replaced with the computerized system to give more convenience to the student and the lecturer. When students hand over their assignment/project the operator will keep the records of the submission details. Emails will be sent to the students to verify their submission. The same goes for the marked and collected assignment/project. In addition, the lecturer will be informed to check the submission records of the students. By doing this, the assignment/project is always kept in safe condition after the submission. The proposed system also helps lecturer to keep track of their student submission. The lecturer can check the time of submission and enable the student to collect their assignment/project after being marked. This system will improve the management of student assignment/project at the university.